Impact of deep brain stimulation on cognition in Alzheimer's patients (Research, Society and Development, 2024)
Alzheimer's disease (AD) is a progressive and chronic disorder, characterized by the destruction of cholinergic neurons, and is one of the main causes of dementia in the world. Deep brain stimulation (DBS) is effective in treating symptoms and features of various disorders, including Parkinson's disease, essential tremor, dystonia, epilepsy, and obsessive-compulsive disorder, and is currently being explored for use in other disorders, including Alzheimer's disease, obesity, anorexia nervosa, among others. In addition to altering local and network-wide circuitry, there is growing evidence that DBS may also have neuroprotective effects. The present work is constituted under the format of a Systematic Review, which is used as a tool to summarize, evaluate and communicate the results and implications of a large amount of research and information. The promising results of some studies highlight the urgent need for larger-scale RCTs with larger sample sizes and more standardized stimulation parameters to understand whether PES can become an innovative treatment for AD. This study aims to describe the occurrence of cases in which DBS, in patients with Alzheimer´s, had an impact on the social cognition and quality of life of this population group.